Job Satisfaction And Work-life Quality Among Employees Of Hotel Industry In Malaysia - Farah Laili Muda @ Ismail; Anita Ismail; Nor Ailis Abd Wahab; Latifah Abdul Latiff (IAEME Publication, 2024)
International Journal of Civil Engineering and Technology, 10(04), 2019, pp. 2285-2293